Janus Associated Kinases Inhibitors in the Pharmacological Thera - Daniela Santos1; Sofia Mendes; Manuel Morgado (Formifarma, LDA., 2017)
Janus associated kinases inhibitors are a new strategy for the treatment of different clinical conditions like immunologic, inflammatory and oncology disorders. The aim of this study was to perform a review of all Janus associated kinases inhibitors available in national and international pharmaceutical market, their therapeutic indications and adverse effects, and the potential indications for investigation of those already available in the pharmaceutical market. It was also performed a review of the main new Janus associated kinases inhibitors that are still in clinical research. A literature review was conducted by consulting the summary of product characteristics of Janus associated kinases inhibitors available in the pharmaceutical market and a research in the bibliographic database PubMed using the terms «JAK inhibitors», «Janus associated kinases inhibitors» and «Janus kinases inhibitors». Ninety-five publications were included in the present review, published from January 2014 to January 2015. Drug databases of the European Medicines Agency and United States Food and Drug Administration were also consulted to search for Janus associated kinases inhibitors authorized in clinical practice. Currently, ruxolitinib and tofacitinib are available in the pharmaceutical market and oclatinib is approved as a veterinary medicinal product. Both drugs approved for human use have major adverse effects at hematological and immunological levels, which enhance the importance of the pharmacist's role in the monitoring of patients involved in these treatments. However, several molecules are in pre-clinical and clinical studies trying to prove its potential in the treatment of several immunologic, inflammatory and oncology disorders. Thus, it is still necessary to deepen the knowledge in this area in order to overcome the risks of therapy with these agents. These risks weighed against the benefits of its clinical use have compromised the progress of various Janus associated kinases inhibitors with therapeutic potential.